2019
DOI: 10.17245/jdapm.2019.19.6.379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pain catastrophizing and anxiety on analgesic use after surgical removal of impacted mandibular third molars

Abstract: Background: In dentistry, pain is a factor that negatively affects treatments and drug use. The aim of this study was to evaluate the correlations of the postoperative analgesic use with pain catastrophizing and anxiety in patients who underwent removal of an impacted mandibular third molar. Methods: We recruited 92 patients who underwent the extraction of impacted mandibular third molar. In this study, the Pederson index was used to preoperatively determine the difficulty of surgical extraction. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
2
10
1
1
Order By: Relevance
“…The results of the present study showed that postoperative analgesic use may be higher in patients with high PCS-T scores. The data in the present study are in agreement with the data in Altan et al 16 study. When the groups were examined, it was observed that PCS-T values were significantly higher in those who drank more than one painkiller per day.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results of the present study showed that postoperative analgesic use may be higher in patients with high PCS-T scores. The data in the present study are in agreement with the data in Altan et al 16 study. When the groups were examined, it was observed that PCS-T values were significantly higher in those who drank more than one painkiller per day.…”
Section: Discussionsupporting
confidence: 94%
“…Although it was not statistically significant according to the results of the study, it was observed that the use of analgesics was statistically higher in patients with higher PCS-T scores. They concluded that the preoperative anxiety level was significantly higher in female patients compared to male patients 16 . The results of the present study showed that postoperative analgesic use may be higher in patients with high PCS-T scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study on Twitter, Johnsen et al [ 12 ] reported that more negative words were used in the tweets about dentists than medical doctors and that the words related to pain were used at higher rates. Pain is an unpleasant sensory and emotional experience, and it has different personal effects on different people [ 13 14 ]. Gao et al [ 15 ] reported that aversive dental treatment, indirect learning through parents and peers, and exposure to negative information affected dental anxiety and fear.…”
Section: Discussionmentioning
confidence: 99%
“…The medical history was checked for any previously unnoticed systemic problems. The difficulty score of the surgery was assessed according to Pederson's score on a panoramic X-Ray [ 31 ], and the maximum mouth opening (mm), was measured by the operator with a Vernier Caliper as the distance between the upper and lower incisors. All the patients were asked to do a Chlorhexidine 0.12% mouthwash 15 min before the operation [ 32 , 33 ], and 40 patients (group two & four) received 2 ml of Dexamethasone Sodium phosphate 4 mg/1 ml (Dexamethasone Medis®) via IM route (Deltoid muscle site) half an hour before surgery.…”
Section: Methodsmentioning
confidence: 99%